Automatic soup adding device for hot pot - XIE CHUWEN (2021)
The invention discloses an automatic soup adding device for a hot pot. The device comprises a container used for containing soup bases and a support used for supporting the container, a plug used for sealing is arranged at an opening of the container, two holes are formed in the plug, a balance pipe used for balancing air pressure inside and outside the container is inserted into one through hole, a feeding pipe used for conveying the soup bases in the container to the hot pot is inserted into the other through hole, and an adjuster used for adjusting the flow speed of the soup bases is arranged on the feeding pipe. The soup adding device can replace manual soup adding for the hot pot, and the labor cost of a hot pot restaurant is saved; according to the device, the soup bases are continuously added into the pot at a slow speed, the mass of the cold soup base flowing into the pot (or dropping into the pot) is extremely small compared with that of original soup in the pot, and the temperature can quickly reach